2021
DOI: 10.13102/sociobiology.v68i1.4973
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Epigaeic Ant Assemblage Structure in the Amazon during Successional Processes after Bauxite Mining

Abstract: Environmental impact studies often involve monitoring and using bioindicators to evaluate the restoration stage of impacted areas. We aimed to assess ant assemblages’ response to the ecological succession of previously disturbed areas in the Brazilian Amazon. We sampled epigeic ant assemblages in five bauxite mining areas, representing different restoration stages, and compared them with two pristine areas. We also compared trends in species richness at the same mine site investigated 14 years earlier. Ten pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…The preliminary results presented here, indicating a cutback in the functional spectrum matching the gradient of disturbance, corroborates this idea. The trends observed here concur with other works focusing on the Amazon (Fernandes et al, 2021; Fontenele & Schmidt, 2021), other Brazilian biomes (Leal et al, 2012; Martello et al, 2018), but also other regions of the world (González et al, 2018). We found that dissimilar patterns and responses were displayed by specific versus generalist functional traits, for example, specialised traits were particularly eroded in assemblages of disturbed ecosystems while generalist traits seem unscathed.…”
Section: Discussionsupporting
confidence: 92%
“…The preliminary results presented here, indicating a cutback in the functional spectrum matching the gradient of disturbance, corroborates this idea. The trends observed here concur with other works focusing on the Amazon (Fernandes et al, 2021; Fontenele & Schmidt, 2021), other Brazilian biomes (Leal et al, 2012; Martello et al, 2018), but also other regions of the world (González et al, 2018). We found that dissimilar patterns and responses were displayed by specific versus generalist functional traits, for example, specialised traits were particularly eroded in assemblages of disturbed ecosystems while generalist traits seem unscathed.…”
Section: Discussionsupporting
confidence: 92%
“…The ant population in areas where human mining is present has been used as a biological indicator of environmental remediation in many studies [40][41][42][43][44] based on the population and the number of species that thrive in the area of mining operations relative to the native species in the area (in the upper part of Figure 8). Special traps are placed in the mine under consideration to measure the ant population, and these are compared with corresponding traps in a reference site from an area without human intervention.…”
Section: Mine Rehabilitationmentioning
confidence: 99%
“…Ottonetti et al [43] suggested suitable ant species for biomarkers in restored Mediterranean mines. • The same technique was used by Fernandes et al [44] to study the evolution of bauxite mine reclamation in the Amazon. • The study of Khazin et al [45] uses two inhabitant species of ants as bioindicators:…”
mentioning
confidence: 99%
See 1 more Smart Citation